Effects of Rock Inhibitor (Y-27632) on the Corneal Endothelium in Dogs Undergoing Phacoemulsification: A Pilot Study - Rosa Filezio, Marcella [UNESP]; R. M. Pádua, Ivan [UNESP]; Madruga, Gabriela [UNESP]; Fachini, Fanchimery [UNESP]; Moura dos Santos, Daniela [UNESP]; E. H. Bueno, Karina [UNESP]; Laus, José Luiz [UNESP]; Castro Moraes, Paola [UNESP] (Wiley, 2025)
Cataract is one of the most common ocular conditions in dogs, and phacoemulsification is the preferred therapeutic method among ophthalmologists. Of all postoperative complications, endothelial injuries stand out, potentially leading to permanent corneal decompensation and loss of transparency. In this study, we evaluated the effects of the ROCK inhibitor (Y-27632) on endothelial protection in dogs undergoing phacoemulsification. Twenty eyes of 10 dogs with bilateral senile cataracts were divided into two groups: Control Eyes (CE) (n = 10), which received balanced saline solution (BSS), and Treated Eyes (TE) (n = 10), which received 0.3 mL of intracameral Y-27632 at a concentration of 100 μmol/L immediately after corneal suturing. The corneal endothelium was evaluated through non-contact specular microscopy before and at different time points after phacoemulsification. We analyzed endothelial cell density (cells/mm2) and cell area (μm2), corneal thickness (mm), hexagonality (%), and coefficient of variation of cell size (%). P values equal to or < 0.05 were considered significant. Both groups showed a loss of endothelial cell density without statistical difference. Regarding corneal thickness and hexagonality, there was no difference. In the CE group, the cell area increased significantly between the evaluated time points, which was not observed in the TE group. It is assumed that the intracameral application of 0.3 mL containing 100 μmol/L of Y-27632 during phacoemulsification in dogs contributes to the stability of corneal endothelial cells, reducing their loss (7.4%), although no significant decrease in cell loss was observed compared to its non-use (11.8%).
Keywords: cataract; corneal endothelium; dogs; phacoemulsification; ROCK inhibitor (Y-27632)